Venous thromboembolism occurring during adolescence. Issue 5 (19th January 2016) - Biss, Tina; Alikhan, Raza; Payne, Jeanette; Alamelu, Jayanthi; Williams, Michael; Richards, Michael; Mathias, Mary; Tunstall, Oliver; Chalmers, Elizabeth
Abstract : Objective: Risk assessment for venous thromboembolism (VTE) and thromboprophylaxis in those with risk factors is established in adult practice. Evidence to support efficacy and safety of this approach in adolescents is lacking. We aimed to describe thrombotic risk factors and to determine the proportion of potentially preventable events in a retrospective cohort study of adolescents with VTE. Design, setting and patients: Data were collected between 2008 and 2014 from eight tertiary UK centres. Qualifying events were radiologically confirmed VTE in subjects aged 12–17 years. Central venous line-related upper venous system events were excluded. Results: 76 cases were identified, 41 males, median age 15 years. Frequent risk factors were: reduced mobility, 45%; thrombophilia, 24%; malignancy, 20%; surgery, 18%; combined oral contraceptive pill, 12%; congenital venous anomaly, 5%. 28 (37%) had no significant underlying diagnosis and no provoking event/hospitalisation, presenting as outpatients with VTE which was considered 'unpreventable'. Of 48 where there had been opportunity for risk assessment, chemical thromboprophylaxis was not indicated in 26 and was contraindicated in 8. 14/76 (18%) had an indication to consider thromboprophylaxis and no contraindication. Of these, four had cerebral palsy, five malignancy and two inflammatory bowel disease. All had reduced mobility with recent surgery in eight. Four received chemical thromboprophylaxis prior to presentation. Conclusions: Among a cohort of adolescents with VTE, a small proportion (13%) had an indication to consider chemical thromboprophylaxis but did not receive it. VTE risk assessment and prevention should focus on adolescents with immobility or surgery, particularly in those with malignancy.